High-dose vitamin D3 supplementation is a requisite for modulation of skin-homing markers on regulatory T cells in HIV-infected patients - Khoo, Ai-Leng; Koenen, Hans J P M; Michels, Meta; Ooms, Sharon; Bosch, Marjolein; Netea, Mihai G; Joosten, Irma; van der Ven, André J A M (AIDS research and human retroviruses, 2013)
Vitamin D(3) is known to have an effect on the immune function. We investigated the immunomodulatory capability of vitamin D(3) in HIV-infected patients and studied the expression of chemokine receptors on regulatory T cells (Treg). Vitamin D(3)-deficient HIV-1-seropositive subjects were treated with cholecalciferol (vitamin D(3)) at a dose of 800 IU daily for 3 months (n=9) or 25,000 IU weekly for 2 months (n=7). Peripheral blood mononuclear cells (PBMCs) were isolated and analyzed for skin-homing (CCR4 and CCR10) and gut-homing (CCR9 and integrin α(4)β(7)) marker expression on Treg, by flow cytometry, before and after supplementation. Serum 25(OH)D(3) and parathyroid hormone (PTH) levels were determined at baseline and after the treatment period. Weekly doses of 25,000 IU cholecalciferol effectively achieved the optimal target serum 25(OH)D(3) concentration of >75 nmol/liter (30 ng/ml) in HIV-infected patients. High-dose cholecalciferol supplementation differentially influenced skin-homing markers on Treg with an increased level of CCR10 expression and while a reduction in CCR4 expression level was observed together with a lower percentage of Treg expressing CCR4. For both dosing regimens, there were no significant differences in the expression of gut-homing markers, CCR9, and integrin α(4)β(7). High-dose vitamin D(3) supplementation is needed to reverse vitamin D(3) deficiency in HIV-infected individuals and this results in modulation of skin-homing markers but not gut-homing markers expression on Treg. At a standard dose of 800 IU/day, vitamin D(3) is not effective in achieving an optimal 25(OH)D(3) concentration in patients with an underlying T cell dysfunction and is unable to exert any immunomodulatory effects.